The effect of intraportal prostacyclin infusion on hepatic glycogen content in liver transplantation [KARACIGER TRANSPLANTASYONUNDA INTRAPORTAL PROSTASIKLIN INFUZYONUNUN KARACIGER GLIKOJEN DUZEYINE ETKISI] - (:unkn) unknown (AVES, 1996)
It was demonstrated that glycogen stores could be rapidly repleted in pig by intraportal infusions of glucose and prostacyclin during donor operation. Livers from nutritionally repleted animals are less susceptible to injury originating from cold ischemia and this may also improve the posttransplant initial function. Prostacyclins have long been known as a cytoprotector and they can regulate the hepatic microcirculation. The aim of this study is to determine whether the infusion of prostacyclin and glucose have synergistic action on hepatic glycogen content. Two groups of pig were replenished nutritionally either glucose (group 1) or glucose + prostacyclin (group 2) by portal route during donor operation. Hepatic glycogen content was found to be significantly increased in group 2 when compared with group 1, and values were maintained higher during the operative procedure. It is concluded that glucose and prostacyclin infusions may be useful for the glycogenisation of donor liver ad may improve the outcome of transplantation.
Keywords: Glycogen; Liver transplantation; Prostacyclin